GeoGebra utilization training for visualization of solid geometry volume formula constructions for mathematics teachers - Yuwono, Muhammad Ridlo; Triyono, Triyono; Wijayanti, Septiana; Tasari, Tasari; Sungkono, Joko; Syaifuddin, M. Wahid; Yuliana, Yuliana; Firmansah, Fery; Perdana, Muhammad Ikhsan Habib; Prameswari, Lala Areta (Universitas Muhammadiyah Magelang, 2025)
This community service was conducted to improve mathematics teachers' skills in using GeoGebra to visualize the volume formula constructions of solid geometry shapes, particularly cubes, cuboids, and pyramids. The service activity was packaged in the form of training conducted online from July 20, 2024, to July 27, 2024, via Zoom Meeting. The results of this workshop showed that participants were able to use the tools available in GeoGebra to create visualizations of the volume formula constructions of solid geometry shapes. This activity had a positive impact on increasing the knowledge and skills of mathematics teachers in utilizing GeoGebra as a learning medium for geometry materials.